Preparation method of high-purity flaky vanadium pentoxide

Through the ammonization transformation of sodium vanadate solution and multi-step impurity removal process, high-purity vanadium pentoxide was prepared, which solved the problems of low product qualification rate and high cost in the existing technology, and achieved high efficiency, low cost and Clean production process.

CN119490224APending Publication Date: 2025-02-21HEBEI IRON AND STEEL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566954.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art has problems such as low product qualification rate, large quality fluctuations, difficult removal of heavy metal impurities and high cost in the industrial production of high-purity vanadium pentoxide, which is difficult to meet the large-scale, low-cost and cleanliness of aviation-grade vanadium. Production requirements.

Method used

Through the ammonization transformation of sodium vanadate solution, cooling crystallization, dissolving impurities, recrystallization and calcining of fuse sheets, high-purity vanadium pentoxide with a purity of ≥99%, and generated by chromium removal agent and reduction smelting Ferrochromium alloy realizes the recycling of sodium and water media.

Benefits of technology

It realizes efficient preparation of high-purity flake vanadium pentoxide, reduces production costs, improves product qualification rate and quality stability, and reduces resource consumption and environmental pollution through recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490224A_ABST
    Figure CN119490224A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of high-purity flaky vanadium pentoxide. The preparation method comprises the following steps: carrying out ammoniation reaction on a sodium vanadate solution, and cooling and crystallizing to obtain a low-purity ammonium metavanadate solid phase; the ammonium metavanadate solid phase is subjected to dissolution, impurity removal and recrystallization to obtain high-purity ammonium metavanadate and post-crystallization liquid, and the high-purity ammonium metavanadate is subjected to drying, calcination and piece melting to obtain high-purity flaky vanadium pentoxide; and adding a chromium removing agent into the crystallized liquid to obtain an iron-chromium-rich solid phase, and carrying out reduction smelting to obtain the ferrochrome alloy. The high-purity flaky vanadium pentoxide with the purity larger than or equal to 99% is obtained and can be used for smelting high-purity vanadium-aluminum alloy; a sodium salt solution obtained by ammonium transformation is subjected to evaporative crystallization, and is returned to sodium salt roasting and water leaching vanadium extraction for reuse, so that cyclic utilization of sodium and water media is realized; and the iron-chromium-containing solid phase obtained by adding the chromium removing agent into the crystallized liquid is reduced and smelted to generate the ferrochrome for special steel production, and the method has good economic benefits and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of vanadium chemical metallurgy, and in particular to a method for preparing high-purity flaky vanadium pentoxide. Background Art

[0002] High-purity flake vanadium pentoxide is the basic raw material for the production of vanadium aluminum alloys for aerospace. The requirements for vanadium pentoxide raw materials for aerospace vanadium aluminum alloys are strict: the shape is flake, the V2O5 content is ≥99%, and there are clear requirements for 25 impurity elements, among which the Cr content is ≤0.02%, the Mo content is ≤0.01%, the As content is ≤0.005%, and the Na2O+K2O is ≤0.3%. Due to the low-cost preparation technology of high-purity vanadium products, my country mainly relies on imports, which seriously restricts the independent and high-quality development of domestic aerospace, especially the domestic large aircraft industry.

[0003] At present, the domestic industrial production method of high-purity flake vanadium pentoxide is to control the impurities such as Si, Fe, P, K / Na in aviation-grade flake vanadium by improving the iron removal process of vanadium slag, applying the new aluminum method for impurity removal and vanadium precipitation process, optimizing the melting and casting process, etc., but there are still problems such as low product qualification rate, large quality fluctuations, difficulty in removing heavy metal impurities such as Cr, As, Mo, and high cost. Most of the other domestic high-purity flake vanadium pentoxide preparation technologies remain in the laboratory research and development stage, represented by extraction method, multi-stage chemical impurity removal, ion exchange method, etc., all of which have problems such as too long process chain, large one-time investment, high implementation cost, and difficult disposal of large amounts of wastewater, which are difficult to meet the requirements of large-scale, low-cost, and clean production of aviation-grade flake vanadium. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing high-purity flake vanadium pentoxide, which has a small amount of wastewater and low cost and meets the requirements of clean production.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] (1) adding ammonium carbonate or ammonium bicarbonate to the purified and impurity-removed sodium vanadate solution to carry out an ammoniation reaction, and then cooling and crystallizing to obtain a low-purity ammonium metavanadate solid phase and a sodium salt solution;

[0007] (2) adding the ammonium metavanadate solid phase into pure water to dissolve it, and then filtering and separating it to obtain a decontaminated solid phase and an ammonium metavanadate solution; and the ammonium metavanadate solution is recrystallized to obtain a high-purity ammonium metavanadate solid phase and a post-crystallization liquid.

[0008] (3) High-purity ammonium metavanadate is dried, calcined, and fused to obtain high-purity flake vanadium pentoxide.

[0009] (4) adding a chromium removal agent to the liquid after crystallization, and then filtering and separating to obtain a solid phase rich in iron and chromium, and reducing and smelting the solid phase to obtain a ferrochrome alloy.

[0010] The reaction temperature of the ammonium reaction in step (1) of the present invention is 40-95° C., the reaction time is 5-60 min, the vanadium concentration in the sodium vanadate solution is 15-40 g / L, and the molar ratio of ammonium ions in ammonium carbonate or ammonium bicarbonate to vanadium in the solution is 1-1.3:1.

[0011] In step (1) of the present invention, if ammonium carbonate is used for the ammoniation reaction, the sodium salt solution is evaporated and crystallized to obtain sodium carbonate and condensed water, the condensed water is returned to the leaching process of water leaching vanadium, and the sodium carbonate is returned to the mixing process of sodium calcination. If ammonium bicarbonate is used for the ammoniation reaction, the sodium salt solution is evaporated, crystallized and calcined to obtain sodium carbonate and condensed water, the condensed water is returned to the leaching process of water leaching vanadium, and the sodium carbonate is returned to the mixing process of sodium calcination.

[0012] The dissolution process in step (2) of the present invention requires a liquid-to-solid volume ratio of 3-6:1, a temperature of 60-95° C., and a time of 10-60 min.

[0013] The step (2) of the present invention can be repeated 1-3 times to improve the purity of ammonium metavanadate.

[0014] The chromium removal agent in step (4) of the present invention is a mixture of nano-ferroferric oxide and biomass carbon material, the mass content of the biomass carbon material is 10%-50%, the addition amount is 0.3-2g / L, the chromium removal time is 30-150min, and the biomass carbon material includes one or more of chitosan, activated carbon, jute, graphene oxide, and de-oiled soybean.

[0015] In the reduction smelting process in step (4) of the present invention, a reducing agent is added according to the content of the biomass carbon material to fully reduce iron and chromium to obtain a ferrochrome alloy.

[0016] In step (4) of the present invention, the reducing agent is one or both of blue charcoal and coke, and the amount of the reducing agent added is (reducing agent + total carbon molar amount in biomass carbon material) / (iron + chromium molar amount) is 1.5-2.5:1.

[0017] In the step (4) of the present invention, the filtrate after chromium removal from the crystallized liquid is returned to the dissolution and impurity removal step for recycling.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects:

[0019] (1) Through the process of sodium vanadate solution ammonium transformation - cooling crystallization - dissolution and impurity removal - recrystallization - calcination of melt flakes, high-purity flake vanadium pentoxide with a purity of ≥99% is obtained, which can be used for high-purity vanadium aluminum alloy smelting;

[0020] (2) The sodium salt solution obtained by ammoniation transformation of sodium vanadate solution is evaporated and crystallized, and then returned to sodium calcination and water leaching for vanadium extraction, thus realizing the recycling of sodium and water medium;

[0021] (3) After the crystallization, the chromium-containing solid phase obtained by adding a chromium removal agent is reduced and smelted to form a chromium-iron alloy, which is used in the production of special steel products and has good economic benefits and application prospects;

[0022] (4) After the crystallization, the filtrate after chromium removal can be returned to the dissolution and impurity removal process, thus realizing the recycling of the water medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0024] The following will combine the specific Figure 1 Specific embodiments of the present invention are described in detail. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.

[0025] Example 1

[0026] (1) A purified sodium vanadate solution having a vanadium concentration of 20 g / L is taken. Ammonium carbonate is added to the solution at 60°C for an ammoniation reaction for 30 min, and the molar ratio of ammonium ions to vanadium in the solution is 1.1:1. After cooling and crystallization, a low-purity ammonium metavanadate solid phase and a sodium salt solution are obtained.

[0027] (2) adding the ammonium metavanadate solid phase into pure water at a liquid-to-solid volume ratio of 4:1, dissolving at 75°C for 30 minutes, and then filtering and separating to obtain a decontaminated solid phase and an ammonium metavanadate solution. The ammonium metavanadate solution is subjected to a single recrystallization to obtain a high-purity ammonium metavanadate solid phase and a post-crystallization liquid.

[0028] (3) Drying, calcining and melting high-purity ammonium metavanadate to obtain high-purity flake vanadium pentoxide.

[0029] (4) Add a mixture of nano-ferroferric oxide and biomass carbon material (chitosan) to the post-crystallization liquid, the mass content of chitosan is 10%, the addition amount is 1g / L, and the chromium removal time is 90min. Filter and separate to obtain a solid phase rich in iron and chromium, perform reduction smelting on the solid phase, add a blue charcoal reducing agent, the addition amount is such that the total carbon molar amount of chitosan and blue charcoal is 2.5 times the total molar amount of iron and chromium, and obtain a ferrochrome alloy.

[0030] After testing, the main components of high-purity flake vanadium pentoxide are shown in the following table.

[0031] element <![CDATA[V2O5]]> As Mo Cr <![CDATA[Na2O+K2O]]> Mass content (%) 99.65 0.0019 0.0014 0.0062 0.034

[0032] The chromium content of ferrochrome alloy is 53.4%, the C content is 0.06%, and the Si content is 1.54%.

[0033] Example 2

[0034] (1) A sodium vanadate solution with a vanadium concentration of 30 g / L was prepared, and ammonium bicarbonate was added at 80°C for ammoniation reaction. The reaction time was 45 min, and the molar ratio of ammonium ions to vanadium in the solution was 1.2:1. After cooling and crystallization, a low-purity ammonium metavanadate solid phase and a sodium salt solution were separated.

[0035] (2) Add the ammonium metavanadate solid phase into pure water at a liquid-solid volume ratio of 5:1, dissolve it at 85°C for 40 minutes, and filter to obtain the impurity-free solid phase and ammonium metavanadate solution. The ammonium metavanadate solution is recrystallized twice to obtain a high-purity ammonium metavanadate solid phase and a post-crystallization liquid.

[0036] (3) Drying, calcining, and melting the high-purity ammonium metavanadate to produce high-purity flake vanadium pentoxide.

[0037] (4) Add a mixture of nano-ferroferric oxide and biomass carbon materials (activated carbon and jute) to the liquid after crystallization, with the weight of activated carbon and jute accounting for 10% each, the addition amount is 1.5g / L, and the chromium removal time is 120min. After filtration and separation, the solid phase rich in iron and chromium is reduced and smelted, and coke reducing agent is added, and the total carbon molar amount of coke, activated carbon and jute is twice the total molar amount of iron and chromium to obtain ferrochrome alloy.

[0038] After testing, the main components of high-purity flake vanadium pentoxide are shown in the following table.

[0039] element <![CDATA[V2O5]]> As Mo Cr <![CDATA[Na2O+K2O]]> Mass content (%) 99.54 0.0008 0.0014 0.013 0.028

[0040] The chromium content of ferrochrome alloy is 55.7%, the C content is 0.08%, and the Si content is 1.57%.

[0041] Example 3

[0042] (1) A sodium vanadate solution with a vanadium concentration of 15 g / L was selected, and an ammonium carbonate was used to carry out an ammoniation reaction at 45°C for 50 min, and the molar ratio of ammonium ions to vanadium in the solution was 1:1. The corresponding product was obtained by cooling and crystallization.

[0043] (2) Add the ammonium metavanadate solid phase into pure water at a liquid-solid volume ratio of 3:1, dissolve at 65°C for 50 minutes, and separate by filtration to obtain the impurity-free solid phase and the ammonium metavanadate solution. The ammonium metavanadate solution is recrystallized three times to obtain a high-purity ammonium metavanadate solid phase and a post-crystallization liquid.

[0044] (3) The high-purity ammonium metavanadate is subsequently treated to obtain high-purity flake vanadium pentoxide.

[0045] (4) Add a mixture of nano-iron tetroxide and biomass carbon material (graphene oxide) to the liquid after crystallization, the mass proportion of graphene oxide is 30%, the addition amount is 0.8g / L, and the chromium removal time is 100min. After filtration and separation, reduction smelting is performed, and blue charcoal is added in an amount such that the total carbon molar amount of blue charcoal and graphene oxide is 1.8 times the total molar amount of iron and chromium, to obtain a ferrochrome alloy.

[0046] After testing, the main components of high-purity flake vanadium pentoxide are shown in the following table.

[0047] element <![CDATA[V2O5]]> As Mo Cr <![CDATA[Na2O+K2O]]> Mass content (%) 99.38 0.0016 0.0054 0.019 0.037

[0048] The chromium content of ferrochrome alloy is 57.3%, the C content is 0.1%, and the Si content is 1.62%.

[0049] Example 4

[0050] (1) Take a sodium vanadate solution with a vanadium concentration of 35 g / L, add ammonium bicarbonate at 90°C for ammoniation reaction, the reaction time is 20 min, and the molar ratio of ammonium ions to vanadium in the solution is 1.3:1. After cooling and crystallization, separate the product.

[0051] (2) The ammonium metavanadate solid phase was added to the crystallized liquid after chromium removal in Example 1 at a liquid-to-solid volume ratio of 6:1, dissolved at 95° C. for 15 min, and filtered to separate the impurity-removed solid phase and the ammonium metavanadate solution. The ammonium metavanadate solution was recrystallized twice to obtain a high-purity ammonium metavanadate solid phase and a crystallized liquid.

[0052] (3) Drying, calcining, and melting the high-purity ammonium metavanadate to obtain high-purity flake vanadium pentoxide.

[0053] (4) Add a mixture of nano-ferroferric oxide and biomass carbon material (de-oiled soybean) to the liquid after crystallization, the mass proportion of de-oiled soybean is 40%, the addition amount is 1.8g / L, and the chromium removal time is 140min. After filtration and separation, reduction smelting is carried out, and coke reducing agent is added, and the addition amount is 1.7 times the total molar amount of carbon of coke and de-oiled soybean is 1.7 times the total molar amount of iron and chromium to obtain ferrochrome alloy.

[0054] After testing, the main components of high-purity flake vanadium pentoxide are shown in the following table.

[0055] element <![CDATA[V2O5]]> As Mo Cr <![CDATA[Na2O+K2O]]> Mass content (%) 99.21 0.0023 0.0065 0.012 0.058

[0056] The chromium content of ferrochrome alloy is 59.1%, the C content is 0.03% and the Si content is 1.51%.

[0057] Example 5

[0058] (1) A sodium vanadate solution with a vanadium concentration of 25 g / L was prepared, and ammonium carbonate was added at 70° C. to carry out an ammoniation reaction. The reaction time was 40 min, and the molar ratio of ammonium ions to vanadium in the solution was 1.15:1. The desired product was obtained after cooling and crystallization.

[0059] (2) The ammonium metavanadate solid phase was added to the crystallized liquid after chromium removal in Example 2 at a liquid-to-solid volume ratio of 4.5:1, dissolved at 80°C for 25 minutes, and filtered to separate the impurity-removed solid phase and the ammonium metavanadate solution. The ammonium metavanadate solution was recrystallized twice to obtain a high-purity ammonium metavanadate solid phase and a crystallized liquid.

[0060] (3) Drying, calcining, and melting high-purity ammonium metavanadate to produce high-purity flake vanadium pentoxide.

[0061] (4) Add a mixture of nano-ferroferric oxide and biomass carbon materials (chitosan and activated carbon) to the post-crystallization liquid, with chitosan and activated carbon accounting for 25% by mass, the addition amount is 1.2 g / L, and the chromium removal time is 110 min. After filtration and separation, reduction smelting is performed, and a blue charcoal reducing agent is added in an amount such that the total carbon molar amount of blue charcoal, chitosan and activated carbon is 1.5 times the total molar amount of iron and chromium to obtain a ferrochrome alloy.

[0062] After testing, the main components of high-purity flake vanadium pentoxide are shown in the following table.

[0063] element <![CDATA[V2O5]]> As Mo Cr <![CDATA[Na2O+K2O]]> Mass content (%) 99.15 0.0032 0.0067 0.014 0.187

[0064] The chromium content of ferrochrome alloy is 58.5%, the C content is 0.05%, and the Si content is 1.78%.

[0065] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing high-purity flaky vanadium pentoxide, characterized in that: The following steps are involved: (1) adding ammonium carbonate or ammonium bicarbonate to the purified and impurity-removed sodium vanadate solution to carry out an ammoniation reaction, and then cooling and crystallizing to obtain a low-purity ammonium metavanadate solid phase and a sodium salt solution; (2) adding a low-purity ammonium metavanadate solid phase into pure water to dissolve it, and then filtering and separating it to obtain a decontaminated solid phase and an ammonium metavanadate solution. The ammonium metavanadate solution is recrystallized to obtain a high-purity ammonium metavanadate solid phase and a post-crystallization liquid; (3) drying, calcining and fusing high-purity ammonium metavanadate to obtain high-purity flake vanadium pentoxide; (4) adding a chromium removal agent to the post-crystallization liquid, followed by filtration and separation to obtain a solid phase rich in iron and chromium and a filtrate after the post-crystallization liquid is chromium-removed, and reducing and smelting the solid phase to obtain a ferrochrome alloy.

2. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: The reaction temperature of the ammonium reaction in step (1) is 40-95° C., the reaction time is 5-60 min, the vanadium concentration in the purified and impurity-free sodium vanadate solution is 15-40 g / L, and the molar ratio of ammonium ions in ammonium carbonate or ammonium bicarbonate to vanadium in the solution is 1-1.3:

1.

3. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: Ammonium carbonate is used for ammoniation reaction, and the sodium salt solution is evaporated and crystallized to obtain sodium carbonate and condensed water. The condensed water is returned to the leaching process of vanadium extraction by water leaching, and the sodium carbonate is returned to the mixing process of sodium roasting.

4. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: Ammonium bicarbonate is used for ammoniation reaction, and the sodium salt solution is evaporated, crystallized and calcined to obtain sodium carbonate and condensed water. The condensed water is returned to the leaching process of vanadium extraction by water leaching, and the sodium carbonate is returned to the mixing process of sodium roasting.

5. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: The dissolution process in step (2) requires a liquid-to-solid volume ratio of 3-6:1, a temperature of 60-95° C., and a time of 10-60 min.

6. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: Repeat step (2) 1-3 times.

7. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: In step (4), the chromium removal agent is a mixture of nano-ferroferric oxide and biomass carbon material, the mass content of the biomass carbon material is 10%-50%, the addition amount is 0.3-2g / L, the chromium removal time is 30-150min, and the biomass carbon material includes one or more of chitosan, activated carbon, jute, graphene oxide, and de-oiled soybean.

8. The method for preparing high-purity flaky vanadium pentoxide according to claim 1, characterized in that: In the reduction smelting process in step (4), a reducing agent is added according to the content of the biomass carbon material to fully reduce the iron and chromium to obtain a ferrochrome alloy.

9. The method for preparing high-purity flaky vanadium pentoxide according to claim 8, characterized in that: The reducing agent is one or both of blue charcoal and coke, and the added amount of the reducing agent is (reducing agent + total carbon molar amount in biomass carbon material) / (iron + chromium molar amount) of 1.5-2.5:

1.

10. The method for preparing high-purity flaky vanadium pentoxide as claimed in claim 1, characterized in that: In step (4), the filtrate after chromium removal from the crystallized liquid is returned to the dissolution and impurity removal step for recycling.